Oil Palm Biomass As A Sustainable Energy Source: A Malaysian Case Study. - Siew, Hoong Shuit; Kok, Tat Tan; Keat, Teong Lee (2008)
The latest scientific data confirmed that the earth's climate is rapidly changing. Therefore, it has been widely accepted worldwide that global warming is by far the greatest threat and challenge in the new millennium. The main factor that causes global warming is the release of greenhouse gases to the environment.